Perbedaan Keakraban Suami-istri Berdasarkan Adanya Anak Dengan Kecenderungan Attention Deficit/Hyperactivity Disorder - Sari Dewi A Carla R. Marchira Soewadi (Berita Kedokteran Masyarakat (BKM), 2011)
Background: Prevalence of children with Attention Deficit/ Hyperactivity Disorder (ADHD) tendency often funding at school-age. Children with ADHD often make parent feel stress full. Parent will through some energies and time to control children behavior and to find best treatment for children. As a consequence, spouse feels neglected and its will disturb husband-and-wife relationship and threat marriage stability. Husband-and-wife relationship can influence by another socio-demographic factors.Objective: To analyze the difference of husband-and-wife relationship based on children with ADHD tendency existence and another factor i.e communication, sexual intercourse, spouse personality/ temperament, education, occupation, monthly income, marital-age and number of child those give influence heaviness to husband-and-wife relationship.Method: The type of this study is observational with cross sectional analytic design. The subject is parent of student at elementary school of Karangwuni 1 Yogyakarta representatitively by husband or wife by incidental sampling. ADHD tendency is valued by IOWA Conner’s Rating Scale instrument. The husband-and-wife relationship is valued by Husband-and-Wife Questioner. Hypothesis tests use chi-square and logistic regression.Result: There is no significant difference of husband-and-wife relationship and children with ADHD tendency (X2 = 1,996; p > 0,05). There is significant difference of education factor and husband-and-wife relationship (p < 0,05; OR = 2,79; CI 1,05-7,47).Conclusion: There is no significant difference of husband-and-wife relationship based on children with ADHD tendency existence for parent of student at elementary school of Karangwuni 1 Yogyakarta. Education factor gives significant influence heaviness to husband-and-wife relationship.Keywords: children with tendency attention deficit/ hyperactivity disorder, husband-and-wife relationship